Spatial and temporal variability of precipitation in Tocantins State, Brazil (Research, Society and Development, 2021)
This study aimed to map monthly and annual rainfall based on geostatistical procedures and to analyze spatial and temporal rainfall trends for the state of Tocantins. Historical series of monthly and annual precipitation were constituted in a standardized period between 1988 and 2019, generating average values ​​to proceed with the spatialization and interpolation of the data. The exploratory analysis of the data was performed based on trend graphs for annual precipitation, which demonstrate the general behavior presented in this analysis between the different events under study, submitting the data to the Mann-Kendall trend test. We proceeded with the adjustment of the theoretical semivariogram model, from obtaining the values ​​for the structural parameters such as the nugget effect, the contribution and the reach. For monthly rainfall, the degree of spatial dependence for the models with the best performance varied between 72.4% and 100%. From the spatial point of view, the southeast of Tocantins presented the lowest precipitation values ​​and the month of December the highest. As for the temporal bias, during the month of July, the center-south portion of Tocantins presented very low rates, between 0 and 2 mm, while in the rainiest months, from December to March, the monthly precipitation varied between 382 mm (January) and 262 mm (February). The months between July and September are the critical drought period in Tocantins, when the rainfall in the period varied from 0 to 25 mm.